Dye-Sensitized Solar Cell-Based Photovoltaic Thermal for Ethanol Distillation: A Narrative Review - Aliefia Noor; Meri Hamdini; Salsabila Ramadina; Yuant Tiandho (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
The potential for solar energy in Indonesia is abundant and attractive to be developed into one of the leading renewable energy sources. Photovoltaic or solar cells are devices that can be used to convert solar energy directly into electrical energy. A dye-sensitized solar cell (DSSC) is an exciting type of solar cell to be developed because it is cheap, easy, and can use natural dyes based on plant extracts. However, the performance of DSSC degrades when it is at high operating temperatures. In this article, a narrative review is presented to improve the efficiency of DSSC by integrating with a solar collector in the form of a photovoltaic/thermal (PV/T) system. The solar collector will act as a heat absorbent from the DSSC, and the heat energy obtained will be used to distill ethanol. Optimization in the ethanol distillation system can take advantage of CuO as a nanoparticle in the working fluid or better know as nanofluid.